MENINGKATKAN KEMAMPUAN KOGNITIF ARITMATIKA ANAK DENGAN MENGGUNAKAN ALAT PERAGA PERMAINAN ULAR TANGGA - Hardika Saputra; Ramadhani Dewi Purwanti; Lintang Fitra Utami (LPPM Universitas Bina Bangsa, 2023)
The cognitive aspect of arithmetic ability is a necessary aspect for students that deserves attention. This is because arithmetic cognitive ability is a tool that children will use in facing life. In addition, arithmetic cognitive ability is a basic ability for a child to solve everyday problems and is a tool for further education. Snakes and ladders can be adopted as a learning aid for kindergarten children to improve their counting ability. Teachers can consider using snakes and ladders as a teaching method, as it is considered effective for kindergartners who still have a play instinct. The purpose of this research is to understand the effectiveness of the snakes and ladders learning tool in improving children's counting ability. This research was conducted using qualitative and descriptive methodologies. The population and sample were taken from Group B of Aisyiyah Bustanul Athfal Bumi Mulyo Kindergarten with a total of 16 students. Data collection was done through several ways such as observation, interview, and documentation. The data obtained was then analyzed using several steps, namely; data reduction, data presentation, and conclusion drawing. The results showed that the use of the snakes and ladders tool can help improve arithmetic ability in Group B students of Aisyiyah Bustanul Athfal Bumi Mulyo Kindergarten in the 2021/2022 academic year